Answer:
x = -1
y = -2
( -1, -2 )
Explanation:
6x + 5y = -16
They gave us what "y" is and its....
y = 7x + 5
We substitute the "y" in the equation with this "y = 7x + 5
"
6x + 5y = -16
6x + 5(7x + 5) = -16
Now we need to use the distributive property (multiply what is in the parenthesis by "5")
6x + 5 * 7x + 5 * 5 = -16
6x + 35x + 25 = -16
Combine Like Terms ( 6x and 35x)
41x + 35 = -16
Subtract 25 on both sides
41x + 35 - 25 = -16 - 25
41x = -41
Divide by 41 on both sides to isolate the variable
41x/41 = -41/41
x = -1
Now that we have what "x" is (-1) we can use that to find out what "y" is.
y = 7x + 5
Substitute the x with -1
y = 7x + 5
y = 7(-1) + 5
y = -7 + 5
y = -2
x = -1
y = -2
( x, y )
( -1, -2 )
Hope this helped!
Have a supercalifragilisticexpialidocious day!